2010
DOI: 10.1007/s00107-010-0498-7
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and moisture flux in soft fibreboards

Abstract: The thermal conductivity of several wet and dry processed industrial soft fibreboards was determined at temperatures between 10°C and 30°C. Additionally, the thermal conductivity was tested relative to the moisture content ranging from an oven-dry sample to a moisture content of 85% relative humidity. Furthermore, the water vapour diffusion was investigated to determine the resistance factor and the diffusion coefficient under 'dry cup' and 'wet cup' conditions and the sorptions were tested by means of the sor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 18 publications
3
9
0
1
Order By: Relevance
“…conducted extensive testing of both wet and dry processed wood fibre insulation materials, with a variety of thicknesses, densities, and additives, for a total of 28 products being tested (Sonderegger & Niemz, 2012). Of these, 2 products manufactured through the dry process with PUR-resin and paraffin additives were tested, all of which were 60mm thick and densities of 164 kg/m 3 and 240 kg/m 3 .…”
Section: Wfib Sorption Isothermsmentioning
confidence: 99%
See 3 more Smart Citations
“…conducted extensive testing of both wet and dry processed wood fibre insulation materials, with a variety of thicknesses, densities, and additives, for a total of 28 products being tested (Sonderegger & Niemz, 2012). Of these, 2 products manufactured through the dry process with PUR-resin and paraffin additives were tested, all of which were 60mm thick and densities of 164 kg/m 3 and 240 kg/m 3 .…”
Section: Wfib Sorption Isothermsmentioning
confidence: 99%
“…As previously mentioned, Sonderegger et al conducted extensive testing of WFIB products (refer to Section 2.5.1). Dry cup (cup 0%, chamber 65%) and wet cup (cup 100%, chamber 65%) testing was completed (Sonderegger & Niemz, 2012). The test results indicated that dry processed boards had a higher vapour permeability than wet processed boards.…”
Section: Wfib Vapour Permeancementioning
confidence: 99%
See 2 more Smart Citations
“…With increasing pressure the moisture content decreased. [5] und Kollmann [6] sowie wenige neuere Arbeiten an Industrieplatten von Sonderegger und Niemz [7], [8], [9]. Aus dem Bereich der klassischen Holzwerkstoffe liegen dagegen zahlreiche Untersuchungen an Spanplatten und wenn auch Energie zwischen Stoffen, die sich direkt berühren.…”
Section: Wärme Und Feuchtetransport In Faserstoffenunclassified